Postoperative antibiotic strategies in acute complicated appendicitis: a systematic review - Shinwari, Hussayn; Ewalds-Kvist, Béatrice Marianne; El Boghdady, Michael (Springer Science and Business Media LLC, 2026)
Acute appendicitis is a common surgical emergency, with complicated cases carrying an increased risk of infections and morbidity. Whilst preoperative antibiotics help reduce infections, the optimal postoperative regimen remains undefined. Variability exists in antibiotic choice, route and duration. This review aimed to examine recent evidence on postoperative antibiotic stewardship for complicated appendicitis to guide optimal treatment strategies. A systematic review was conducted in accordance with PRISMA guidelines and registered in the PROSPERO registry. A search on PubMed and Cochrane library databases identified studies on postoperative antibiotic use in appendicectomy. Two independent reviewers screened studies, including RCTs, cohort studies and observational studies. Data extraction covered study characteristics, interventions and outcomes. Risk of bias was assessed using RoB 2 and ROBINS-I, with GRADE used to evaluate evidence certainty. This review included 11 studies with 8361 participants. Shorter intravenous antibiotic courses (2–6 days) were found to be non-inferior to longer regimens in preventing infections and reducing hospital stays. Risk factors for prolonged antibiotic use included disease severity and surgical complexity. In selected patients, oral antibiotics were shown to be equally effective. Shorter intravenous antibiotic courses and early transition to oral antibiotics effectively managed complicated appendicitis, reducing hospital stays and healthcare costs without increasing complications. Individualised treatment decisions based on patient risk factors and intraoperative findings are essential. Tailoring antibiotic regimens to individual patient characteristics remains crucial. These findings support antibiotic stewardship efforts and highlight the need for further research, particularly in high-risk populations